The importance of determining procalcitonin and C reactive protein in different stages of sepsis - Zana Baruti-Gafurri; Hidajet Paçarizi; Bukurije Zhubi; Luljeta Begolli; Valdete Topçiu (Biomolecules & Biomedicine, 2010)
Rapid and early diagnosis of systemic infections is very important for acting on time with an adequate therapy. The aim of this study is to determine the diagnostic importance of procalcitonin (PCT) and C-reactive protein (CRP) of bacterial infections in different stages of sepsis.PCT and CRP have been determined in 45 newborns, 1-21 days of age, with different stages of sepsis, in the centre for prematurely born neonates. These parameters have also been determined for control group, in which there were 10 healthy newborns. Procalcitonin values were significantly increased in neonates with septic shock (92,5 ng/mL; 6,06-200 ng/mL) compared to the systemic inflammatory response syndrome- SIRS (41 ng/mL; 0,28-200 ng/mL), neonatal sepsis (10,26 ng/mL; 1,08-111,3 ng/mL), neonatal sepsis and purulent meningitis (9,80 ng/mL; 4,3-18,9 ng/mL). The control group values were lower than 0,5 ng/mL. CRP is increased without statistical differences in all stages of sepsis in newborns with septic shock (93,2 mg/L; 6,0-196 mg/L) in cases with SIRS (45,64 mg/L; 6,0-147 mg/L), neonatal sepsis (70,02 mg/L; 6-177 mg/L), neonatal sepsis and purulent meningitis (61,98 mg/L; 24-192 mg/L). The average values for the control group were 4,7 mg/L. Procalcitonin is increased in all stages of sepsis with higher values in the septic shock. The increase of PCT levels is related to the severity, course of infection and prognosis of disease.